CREB3L1 deficiency impairs odontoblastic differentiation and molar dentin deposition partially through the TMEM30B - Yuanyuan Li; Yuxiu Lin; Jinqiang Guo; Delan Huang; Huanyan Zuo; Hanshu Zhang; Guohua Yuan; Huan Liu; Zhi Chen (Nature Publishing Group, 2024)
Abstract Odontoblasts are primarily responsible for synthesizing and secreting extracellular matrix proteins, which are crucial for dentinogenesis. Our previous single-cell profile and RNAscope for odontoblast lineage revealed that cyclic adenosine monophosphate responsive element-binding protein 3 like 1 (Creb3l1) was specifically enriched in the terminal differentiated odontoblasts. In this study, deletion of Creb3l1 in the Wnt1+ lineage led to insufficient root elongation and dentin deposition. Assay for transposase-accessible chromatin with high-throughput sequencing (ATAC-seq) and RNA sequencing were performed to revealed that in CREB3L1-deficient mouse dental papilla cells (mDPCs), the genes near the closed chromatin regions were mainly associated with mesenchymal development and the downregulated genes were primarily related to biological processes including cell differentiation, protein biosynthesis and transport, all of which were evidenced by a diminished ability of odontoblastic differentiation, a significant reduction in intracellular proteins, and an even greater decline in extracellular supernatant proteins. Dentin matrix protein 1 (Dmp1), dentin sialophosphoprotein (Dspp), and transmembrane protein 30B (Tmem30b) were identified as direct transcriptional regulatory targets. TMEM30B was intensively expressed in the differentiated odontoblasts, and exhibited a significant decline in both CREB3L1-deficient odontoblasts in vivo and in vitro. Deletion of Tmem30b impaired the ability of odontoblastic differentiation, protein synthesis, and protein secretion in mDPCs. Moreover, overexpressing TMEM30B in CREB3L1-deficient mDPCs partially rescued the extracellular proteins secretion. Collectively, our findings suggest that CREB3L1 participates in dentinogenesis and facilitates odontoblastic differentiation by directly enhancing the transcription of Dmp1, Dspp, and other differentiation-related genes and indirectly promoting protein secretion partially via TMEM30B.